Appelbaum, The Glorious Fourth - An American holiday, and American history - Lewis, Thomas (Teaching History: A Journal of Methods, 1991)
Diana Karter Appelbaum, author of a similar book on Thanksgiving, has written a concise, popular history of Fourth of July celebrations from the Declaration of Independence in 1776 until the 1986 centennial of the Statue of Liberty. She presents a delightful chronicle of how patriotic commemorations have changed to reflect the changing nature of American society. Her thesis is that the national holiday "has been imperialist and nostalgic, frivolous and political, drunken and teetotal, but always, it has been an accurate mirror of the mood of the American people."